Review Article Blastocystosis - Abd AL-Khaliq, Israa Mohammad (AL-Kindy College Medical Journal, 2019)
Blastocystosis is symptomatic infection caused by the protozoal parasite Blastocystis , which resides in the intestinal tract of its hosts and it is one of the most common parasites reported in humans. It’s prevalence ranges between (30 - 50%) of the population in developing countries. This genus has a worldwide distribution and often the most commonly reported human intestinal protozoan in children and adults, even infect infants